2018
DOI: 10.12681/jhvms.18017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different light colors in behavior, welfare parameters and growth performance of Fayoumi broiler chickens strain

Abstract: Research article Ερευνητικό άρθροJ HELLENIC , 69(2): 951-958 ΠΕΚΕ 2018 ABSTRACT. Light is considered one of the most managerial factors affecting poultry well-being. Therefore, the current study was conducted to investigate the effects of different light colors in behaviour, welfare and growth performance of Fayoumi chickens.A total of 300 one-day old chicks of Fayoumi broiler breed were weighed and randomly divided into 4 environmentally controlled chambers with different artificial light color (yellow, red,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…32 Several studies suggested that monochromatic colors, green and blue have positive effect on growth and welfare against to stress especially in poultry management. 7,10 In the present study, the antioxidant enzymes values were increased in groups GL and BL compared to group Control statistically (p<0.05). Animals reared under green light (group GL) had the highest SOD (150.61±9.14), CAT (4.18±0.17) and GPx (186.96±10.50) values compared to group Control and BL (Fig 1b -1c-1d; p<0.05).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…32 Several studies suggested that monochromatic colors, green and blue have positive effect on growth and welfare against to stress especially in poultry management. 7,10 In the present study, the antioxidant enzymes values were increased in groups GL and BL compared to group Control statistically (p<0.05). Animals reared under green light (group GL) had the highest SOD (150.61±9.14), CAT (4.18±0.17) and GPx (186.96±10.50) values compared to group Control and BL (Fig 1b -1c-1d; p<0.05).…”
Section: Discussionsupporting
confidence: 51%
“…5 Many mechanisms are influenced by colors of light, especially growth performance, reproductivity, egg production and quality. 6,7 Color is an important aspect of light due to its effect on several physiological mechanism and behavior in poultry. The artificial colors used for poultry management are named white, red, green and blue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Astuti et al (2015) observed that body weights were increased under blue light treatment without adversely affecting stress indicators. Similarly, Fayoumi chickens maintained under blue light feel better welfare than exposed to yellow, red, green lights (Hesham et al, 2018). Green monochromatic LED resulted in higher body weight marketed up to 7 or 5 week of age male or female respectively (Guevara et al, 2015).…”
Section: Introductionmentioning
confidence: 97%